Hubungan Faktor Individu terhadap Stres Kerja pada Pegawai PT PLN (Persero) UP3 Ternate - Wijoyo, Nurseto Jati; Usman, Usman; Susanto, Arif (J-Mestahat, 2025)
In 2023, 49% of 1,8 million workers in the United Kingdom experienced stress, depression, and anxiety. This indicates that everyone who works can experience work-related stress. This study aims to analyze work-related stress among employees of PT PLN (Persero) UP3 Ternate, determined from the six aspects outlined in the Appendix of the Regulation of the Minister of Manpower of the Republic of Indonesia Number 05 of 2018. The study involved 30 respondents, representing the entire workforce. This research is a quantitative study with a cross-sectional design. The research method uses a survey, with a saturated sampling technique. The survey results show that the overall level of work-related stress felt by employees of PT PLN (Persero) UP3 Ternate is classified as moderate, with an average score of 15,91. The highest factor was related to quantitative workload, with a score of 17,6. A total of 27 respondents experienced moderate work stress. Based on the survey results, it can be concluded that there is a relationship between gender, the workload received, and work stress among employees of PT PLN (Persero) UP3 Ternate in 2024. Providing a balanced workload to all employees and delegating tasks according to their expertise can help reduce stress factors among employees of PT PLN (Persero) UP3 Ternate.